Project-based learning to empower first year medical students - Ismail, Soraya (2021)
This was a poster submitted to the International Putra Innovative Teaching and Learning (PicTL) 2020 poster competition from 22-30 October 2020, organized by University Putra Malaysia. It showcased the 'Mini-poster' project conducted by Year 1 IIUM medical students for the academic year 2019-20202020 while teaching and learning was face-to-face. Embedded is a video of the lecture hall involved showing the mini-posters in the lecture hall. The video was made when the students were learning remotely. This poster won a Gold Medal Award.